Biotechnological Innovations and their Impact on Modern Medicine - Ahmed, Mariam Rafa; Dahham, Tuqa Tariq; Sheaa, Athraa Falah; Mohammed, Safa Jasim (American Journal of Botany and Bioengineering, 2025)
As evidenced by the enormous and rapid growth of industrial and governmental investment in the area of biotechnology over the past decade, it is of little surprise that the application of biotechnologies to modern medicine by the pharmaceutical industry has been immense. The fostering of pharmaceutical biotechnology over the past two decades has gained worldwide acceptance as a means to produce novel, safe, and effective diagnostic tools and drugs. A successful drug development project can take up to 15 years and incur a financial cost on the order of $1.7 billion. Pharmaceuticals continue to be the third highest health-care cost in the United States of America. The development of entirely new drug delivery systems, vaccines, medical imaging agents, and techniques of genetic treatment are the subject of attempts at researching biotechnological solutions. However, the biopharmaceutical revolution of the 20th century, with the approval of more than 300 recombinant dan and peptide products, is likely to make a lasting impact on medical treatment for generations to come. It is also expected that treatments through gene and therapeutic stem cells will have a significant impact on modern medicine. While treating patients on an individual basis with genetically tailored medical care is still well beyond current technology, personalized medicine has started to move away from a “one size fits all” approach to a treatment course that is very much individualized. The achievement of a pharmacogenomic goal will represent a potential enabling tool for advances towards personalized medicine. In addition, other biologically related techniques, such as nanotech, medical robotics, tissue engineering, and regenerative medicine, bioprinting, synthetic biology, and computer-assisted biotechnology design, to name just a few, are the sources of relentless development into modern medicine. Growingly sophisticated modern technology devices have led to the development of a range of medical techniques, such as MRI, used in the prediction, diagnosis, and monitoring of a wide variety of diseases. Due to transplants of organs, mechanical devices, and regenerative medicine approaches, the dramatic increase in life expectancy and the fight against diseases that were previously incurable are examples of improvement in patient health. Advanced biotechnology research methodology has contributed to the knowledge of human disease processes and led to the development of innovative biotechnologies that have previously been utilized for the study of disease. This innovative technical field encompasses recursive acronomic investigations, proteomics, bioinformatics, microarrays, gene therapy, recombinant immunotherapies, and RNAi technologies for use in genetic, protein and metabolite studies within cells, tissue, and assorted body fluids.